ANALISIS NILAI TAMBAH GULA KELAPA DI DESA SIALANG JAYA KECAMATAN BATANG TUAKA KABUPATEN INDRAGIRI HILIR - Nina Sawitri; Yuslizar Yuslizar (Selodang Mayang: Jurnal Ilmiah Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir, 2021)
Coconut sugar processing is one of the agro-industry businesses that is developing in Sialang Jaya Village, Batang Tuaka District, Indragiri Hilir Regency. This business aims to obtain added value from coconut plants. The purpose of this study was to determine the amount of revenue and profits from the coconut sugar processing business and the added value of the coconut sugar processing business in Sialang Jaya Village, Batang Tuaka District, Indragiri Hilir Regency. Analysis of the data used is the analysis of costs, revenues, profits and added value. The results of this study indicate that: (1) The average total cost of the coconut sugar processing business is Rp. 67,351.97 per production, the average revenue is Rp. 202,800.00 per production, the average profit is Rp. 135,448.03 per production. (2) The added value obtained in the coconut sugar processing business is Rp. 4,672.76. The added value ratio obtained is 83.87%. The profit from processing coconut sugar is Rp. 3,024.41 per kg with a profit rate of 64.72%.